Impeachment Mechanisms in Indonesia: Safeguarding Democracy through Presidential and Vice-Presidential Removal - Mursyidi, Mursyidi; Zaini, Syafiudin Kholiq (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
emocracy represents the embodiment of Indonesia’s state system, which upholds popular sovereignty and guarantees the rights of its citizens, including the freedom of association and assembly. These rights are enshrined in the 1945 Constitution of the Republic of Indonesia (UUD 1945), which serves as the foundation for the protection of human rights. The freedom to associate and assemble also serves as an essential means for citizens to determine the direction of national leadership, including the election of the President of the Republic of Indonesia. Within the constitutional system, the President holds a central role as both head of state and head of government. However, after the amendment of the 1945 Constitution, significant changes occurred in the President’s position and accountability mechanism. The President is no longer responsible to the People’s Consultative Assembly (MPR) and cannot be dismissed merely on political grounds or through a vote of no confidence. This study aims to analyze the shift in the President’s position after the constitutional amendments, particularly regarding the impeachment mechanism as stipulated in Articles 7A and 7B of the 1945 Constitution. The research employs a normative legal method with a statute approach and conceptual analysis of legal documents and scholarly literature. The findings reveal that the impeachment mechanism reflects the principle of checks and balances within a modern presidential system. This study contributes to a deeper understanding of constitutional protection, governmental stability, and the rule of law in Indonesia’s democratic practice.